Pengaruh Kemampuan Digital terhadap Kinerja Karyawan pada Bank Syariah Nasional - Hasfi Fathul Hakim Tri Pujiono; Indra Hastuti; Esti Dwi Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2026)
Rapid advancements in digital technology are driving the banking industry, including Islamic banking, to enhance human resource capabilities in order to adapt to increasingly complex job demands. This study aims to examine the influence of digital capability on employee performance at Bank Syariah Nasional. This research employs a quantitative approach with a survey method, involving 60 employees of Bank Syariah Nasional KCS Solo selected through a saturated sampling technique. Data were collected using a questionnaire based on a Likert scale of 1–5, while data analysis was conducted using IBM SPSS version 25, including instrument testing, classical assumption testing, simple linear regression analysis, partial t-tests, and the coefficient of determination. The findings prove that digital capability has a positive and significant effect on employee performance, evidenced by a t-value of 4.550 and a significance level of 0.000, which is below 0.05. The positive regression coefficient of 0.531 indicates that every one-unit increase in digital capability improves employee performance by 0.531 units. The contribution of digital capability in explaining employee performance reaches 26.3 percent, while the remaining percentage is influenced by other external factors such as motivation and work environment. The practical implication encourages Bank Syariah Nasional's management to conduct structured and continuous digital training programs. Furthermore, future researchers are advised to include other variables to gain a more comprehensive understanding of the determinants of employee performance in the era of digital transformation.